(untitled) (Journal of Applied Learning and Teaching, 2024)
Recent disruptions to higher education, including generative artificial intelligence, have highlighted an increased need for student support, particularly to enable a smooth transition during the first year in university. The timing and the tone of support are critical. Here, content expert tutors were embedded in 24 first-year units to provide one-on-one draft assessment feedforward. Tutors received training on using the principle of the pedagogy of kindness; showing concern, compassion, and empathy when interacting with students, and raising academic misconduct concerns. This study evaluated the impact of employing a pedagogy of kindness in tutor sessions on preventing academic integrity issues. Of the 704 draft assessments submitted, 51 students (7%) engaged in a discussion regarding academic integrity. Of these 51 students, 45 students passed their unit, and only one required further investigation for academic misconduct. Tutors proactively contacted students who were identified as at risk of failing their unit. At-risk students who met with a tutor were more likely to pass their subject and achieved a higher average cumulative mark (51% vs 41%, p<0.05). In this paper, we evaluate how tutors employing a pedagogy of kindness increased meaningful learning and student success when incorporating cognitive presence. A responsive strategy using this pedagogical approach was implemented to address the increased use of generative artificial intelligence tools and to decrease the incidence of student academic misconduct.